2017
DOI: 10.1016/j.ajme.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic glutamate receptors (iGluRs) of the delta family (GluD1 and GluD2) and synaptogenesis

Abstract: Glutamate delta-1 (GluD1) and glutamate delta-2 (GluD2) form the delta family of ionotropic glutamate receptors (iGluRs) and are distinct from other (iGluRs) in that they do not exhibit typical agonist-induced ion channel currents. Recent studies have demonstrated a crucial role of the delta receptors in synapse formation by interacting with presynaptic proteins such as Neurexin1. This review presents current knowledge regarding the expression, structure and function of Glu delta receptors (GluD1, GluD2) in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…C-terminal tail domain deletion of GluD1 completely abolishes the receptor's synaptic functioning, while surface expression was not hampered ( Tao et al., 2019 ; Fossati et al., 2019 ). The studies on GluD1 knockout mice have shown that this receptor is essential for normal synapse formation and maintenance of spine dynamics ( Khan, 2017 ). Deletion of this receptor cause abnormality in the LIMK1-cofilin signalling pathway that regulates the actin dynamics through Cofilin-1 activity.…”
Section: Delta Receptors and Actin Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…C-terminal tail domain deletion of GluD1 completely abolishes the receptor's synaptic functioning, while surface expression was not hampered ( Tao et al., 2019 ; Fossati et al., 2019 ). The studies on GluD1 knockout mice have shown that this receptor is essential for normal synapse formation and maintenance of spine dynamics ( Khan, 2017 ). Deletion of this receptor cause abnormality in the LIMK1-cofilin signalling pathway that regulates the actin dynamics through Cofilin-1 activity.…”
Section: Delta Receptors and Actin Cytoskeletonmentioning
confidence: 99%
“…The study has shown that the subunit expression ratio of the NMDAR (GluN2A/GluN2B) is impaired in the GluD1 knockout mice. Future studies are required to understand the detailed molecular mechanistic function of the glutamate delta receptor family influencing the functioning of NMDAR via LIM kinases and cofilin ( Khan, 2017 ).…”
Section: Delta Receptors and Actin Cytoskeletonmentioning
confidence: 99%